Holocene sedimentation offshore Southeast Vietnam based on geophysical interpretation and sediment composition analysis - Hoang Van, Long; Nguyen Tien, Thanh; Vu Tat, Tuan; Nguyen Thanh, Tung; Nguyen Lam, Anh; Dao Bui, Din; Le Van, Duc; Tran Ngoc, Dien; Nguyen Huu, Hiep (Vietnam Journal of Earth Sciences, 2021)
Offshore Southeast (SE) Vietnam is considered a transition zone, with the sedimentary evolution of this area controlled by land-sea interactions, especially by the Holocene sea-level rise. This study presents some new findings regarding Holocene sedimentation and its linkage to the heavy mineral placers within the study area based on high-resolution seismic interpretation and sediment analysis. Our obtained results show that the Holocene sediments directly overlie the Late Pleistocene sedimentary formation, from which they are separated by an erosional/unconformity surface (R1 seismic reflector). Sediments deposited in the Early (~11.7-8.2kyr BP), Middle-Late (8.2kyr BP-present-day) Holocene sub-epochs correspond to the Transgressive and Highstand System tracts, which were closely controlled by the three stages of Holocene sea-level rise. The recent sediments distributed on the seafloor are dominated by sand and gravelly sand, demonstrating high-energy conditions, while the heavy minerals are rich in ilmenite and zircon. Most of these are concentrated along the present shoreline zones, but we do not exclude their accumulation in the paleo-shoreline and incised channels. Two ilmenite dispersion halos (1st and 2nd order) and one zircon dispersion halo (1st order) suggest that ilmenite and zircon are the most dominant heavy minerals while gold is only observed locally. The minerals were potentially derived from the weathering products of the Triassic-Cretaceous ilmenite-, zircon-, and gold-bearing granite and granitoid in central Vietnam.